2021
DOI: 10.3390/ijerph18042142
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Syndrome: Prevalence and Risk Factors among Adolescent Female Intermediate and Secondary Students in Saudi Arabia

Abstract: Background: Metabolic syndrome (MS) has become one of the major challenges to public health worldwide due to its significant association with increased risk of developing type 2 diabetes and cardiovascular disease (CVD) among children and adolescents. Therefore, this study aims to determine the prevalence and risk factors of MS in Saudi adolescents. Methods: This cross-sectional study was conducted in two female National Guard schools (Um Kalthoom Intermediate School and Zainab Bint Jahsh Secondary School) in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 53 publications
2
11
0
2
Order By: Relevance
“…In the present study, it was noticed that MetS early adolescents (aged 10–15 years) had high WC, high triglycerides, high blood pressure, low HDL, and high glucose respectively. These factors are shown to contribute to the increase in cardiometabolic disorders [ 45 , 46 , 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, it was noticed that MetS early adolescents (aged 10–15 years) had high WC, high triglycerides, high blood pressure, low HDL, and high glucose respectively. These factors are shown to contribute to the increase in cardiometabolic disorders [ 45 , 46 , 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…МС стал одной из основных проблем общественного здравоохранения во всем мире в связи с его существенной корреляцией с повышенным риском развития сахарного диабета 2-го типа и сердечно-сосудистых заболеваний у детей и подростков [9]. Исследование A. Alowfi и соавт.…”
Section: международный взгляд на аспекты профилактических мер по борь...unclassified
“…Были проанализированы демографические данные, изучены антропометрические данные (кровяное давление, масса тела, рост, ИМТ и обхват талии), а также биохимический анализ крови натощак (глюкоза и триглицериды плазмы, липопротеиды высокой и низкой плотности). Проведенное исследование показывает, что МС распространен среди детей и подростков женского пола, страдающих ожирением и избыточной массой тела, но также присутствует среди тех, у кого ИМТ в пределах нормальных значений [9].…”
Section: международный взгляд на аспекты профилактических мер по борь...unclassified
“…Three studies were conducted in Jeddah (Taha et al, 2009;Al-Agha et al, 2012;Alowfi et al, 2021), two in Riyadh (Aldhafiri et al, 2012;Al-Hussein et al, 2014), and one in Majmaah (Aldhafiri, 2020). Three studies used the National Cholesterol Education Expert Panel-Adult Treatment Panel (NCEP-ATP III) and WHO criteria for MetS diagnosis (Taha et al, 2009;Aldhafiri et al, 2012;Aldhafiri, 2020), two used the IDF (Al-Hussein et al, 2014;Alowfi et al, 2021), and one used criterion according to (de Ferranti et al, 2004) Table 2 includes the features of the included studies; study designs, MetS prevalence, management, the main outcome, and risk of bias. Of the included studies, four studies were crosssectional studies (Al-Agha et al, 2012;Al-Hussein et al, 2014;Aldhafiri, 2020;Alowfi et al, 2021), and two were cohort studies (Taha et al, 2009;Aldhafiri et al, 2012).…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 99%
“…Of the included studies, four studies were crosssectional studies (Al-Agha et al, 2012;Al-Hussein et al, 2014;Aldhafiri, 2020;Alowfi et al, 2021), and two were cohort studies (Taha et al, 2009;Aldhafiri et al, 2012). The prevalence of MetS among Saudi children ranged from 7% (Alowfi et al, 2021) to 30% (Taha et al, 2009). The included studies reported that the high prevalence of MetS was found in obese children; however, it was also detected in children with normal BMI.…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 99%